Role of Skill India Programs in Fostering Entrepreneurship among Rural Youth in India - Fatima Akther (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Skill India Initiative is the government's primary effort to educate and employ India's youth, particularly those living in rural areas. This initiative has been instrumental in empowering young people in rural India to pursue entrepreneurial endeavors by providing them with the education and training they need to launch successful firms. The Skill India Program provides numerous pathways to gaining marketable expertise in fields as diverse as agriculture, manufacturing, and the service sector. These courses equip participants with the real-world skills and experience crucial to the success of any business initiative. To add to that, the Skill India Program offers budding business owners both financial aid and mentorship services. In addition to low-interest loans, the program offers mentorship and training in areas including business strategy, product promotion, and financial management. The Skill India Program has had a profound effect on business growth in rural areas. It has contributed to the emergence of a new crop of self-reliant, technically proficient, and creative business leaders.